Systemic Risk Caused by the Overlapping Portfolios of Banks Under a Bilateral Network - Gao, Qianqian; Fan, Hong (Frontiers in Physics, 2021)
The frequent financial crises and economic globalization have made systemic risk a hot spot. This paper constructs a dynamic banking system model based on the bank-asset bilateral network. By collecting the balance sheet and portfolio data of 47 Chinese listed banks in 2018, the paper firstly empirically analyses the impact of external shocks, the price-cutting effect, and the proportion of various assets held by banks to their total assets on the systemic risk of the banking system. The risk preference coefficient and systemic shock are then introduced to construct the banks’ quantitative portfolio strategy model to study its optimal investment. It has been found that the greater the external shock and the stronger the price-cutting effect, the higher the systemic risk. Moreover, the external shock and price-cutting effect will have a superimposed effect within a specific range, and systemic risk will increase significantly. The asset classes of the Chinese banking system have a different sensitivity to external shocks, among which loan assets are the most sensitive. Further studies reveal an inflection point of risk preference, resulting in banks’ expected return “increasing first and then decreasing.” The higher the debt-asset ratio, the stronger the banks’ risk tolerance, the more aggressive investment strategies banks can choose to achieve high returns. This paper provides a reference for the banking industry to react to shocks and analyze systemic risk.